DNA-based bead array technology for simultaneous identification of eleven foodborne pathogens in chicken meat - Ratthaphol Charlermroj (2019)
© 2019 Elsevier Ltd A DNA-based bead array method was successfully developed to simultaneously discriminate 11 pathogens namely Listeria grayi, L. innocua, L. ivanovii, L. monocytogenes, L. seeligeri, L. welshimeri, Escherichia coli, E. coli O157:H7, Staphylococcus aureus, methicillin-resistant S. aureus, and Salmonella spp. for multi purposes: food safety, hygiene indication, antibiotic resistance treatment. The bead array technology is based on fluorescent-barcoded paramagnetic beads with unique 24 oligonucleotide (anti-TAG) sequences which can capture biotinylated PCR product with complementary TAG sequence. R-phycoerythrin labeled streptavidin is used to report the presence of the biotinylated PCR products. After optimizing assay conditions, amplification and biotinylation steps can be performed in a single reaction without further purification before hybridization between the biotinylated TAG products and anti-TAG beads. To ensure that the developed method could provide accurate testing with the real food sample, a total of 311 bacterial isolates from 194 chicken meat samples were tested. The results were compared with those from the conventional ISO methods and revealed the relative accuracy, relative specificity, and relative sensitivity of 96%, 100%, and 95%, respectively. Therefore, the developed method was demonstrated to be useful to distinguish 11 bacteria species at the same time with high accuracy, specificity, and sensitivity.